A Household Study of Self-Regulation in Children - Intergenerational Links and Maternal Antecedents - Reinhard Drobetz; Andreas Maercker; C. Katharina Spieß; Gert G. Wagner; Simon Forstmeier (Swiss Journal of Psychology, 2012)
Delay of gratification (DoG) and delay discounting (DD) are behavioral measures of self-regulation and impulsivity. Whereas DoG refers to the postponement of gratification, DD involves the devaluation of a reward over time. Previous studies have demonstrated associations between paternal self-control, paternal personality traits, parenting styles, maternal intelligence, and children's self-regulation. The present study explored intergenerational links between mothers' and child's self-regulation and maternal antecedents of children's DoG. We analyzed 267 mother-child dyads in the German Socio-Economic Panel (SOEP) Children's Study. Measures included an experiment using gummy bears as rewards to assess DoG in children and monetary choice procedures to assess DD in mothers. Additionally, cognitive abilities and personality traits of mothers and children were assessed. The main result was that the children's age and breastfeeding were significant predictors of DoG in children, even when we controlled for other influences such as maternal cognitive abilities and personality traits. We explain the result in the context of previous findings concerning attachment security, bonding, maternal sensitivity, children's self-regulation of energy intake, neuroscientific evidence, and breastfeeding. Further studies should use equivalent measures of DoG in children and parents to further explore this link between breastfeeding and DoG in a genetically sensitive design.
Additional information: This article may not exactly replicate the final version published in the Swiss Journal of Psychology. It is not the version of record and is therefore not suitable for citation. The final version is "A Household Study of Self-Regulation in Children / Reinhard Drobetz, Simon Forstmeier, Andreas Maercker, C. Katharina Spieß, Gert G. Wagner" In: Swiss Journal of Psychology 71 (2012), 4, S. 215-226 2012 by Verlag Hans Huber, Hogrefe AG; online available at http://dx.doi.org/10.1024/1421-0185/a000090
Keywords: 330; breastfeeding; delay discounting; delay of gratification; intergenerational links; maternal antecedents; self-regulation; Kinder